Orthostatic Hypotension in Male Hypertensive Patients: A Cross-Sectional Study at the University of Gondar Comprehensive Specialized Hospital, Gondar, Ethiopia - Getu AA; Abuhay DA; Goshu BT (Dove Medical Press, 2021)
Ayechew Adera Getu,1 Deribew Abebaw Abuhay,2 Bahiru Tenaw Goshu3 1Department of Physiology, College of Medicine and Health Sciences, University of Gondar, Gondar, Amhara, Ethiopia; 2Department of Physiology, College of Medicine and Health Sciences, Debre Tabor University, Debre Tabor, Amhara, Ethiopia; 3Department of Human Anatomy, College of Medicine and Health Sciences, University of Gondar, Gondar, Amhara, EthiopiaCorrespondence: Ayechew Adera Getu Tel +251-91-086-6216Email ayechew.adera@uog.edu.etBackground: Orthostatic hypotension (OH) is defined as a fall in systolic blood pressure (SBP) ≥ 20 mmHg or diastolic BP (DBP) ≥ 10 mmHg within 3 minutes of standing. OH incidence is increased with hypertension, and management of these patients may pose challenges, as treatment of one can worsen the other.Objective: This study aimed to determine the prevalence of OH and its associated factors among male hypertensive patients at the University of Gondar Comprehensive Specialized Hospital, Gondar, Ethiopia.Methods: A hospital-based cross-sectional design was employed. Seated BP was measured twice and the average of the two taken. After BP had been stabilized for 5 minutes, SBP within 3 minutes of standing was measured twice and the minimum of the two taken. A drop of ≥ 20 mmHg in SBP within 3 minutes of standing was taken as OH. All male hypertensive patients who were able to attain a standing position were included. Sociodemographic, anthropometric, and clinical status of the patients were taken using structured interviewer-administered questionnaires. Data were entered and analyzed using SPSS 21. Both bivariate and multivariate logistic regression analysis were done. P≤ 0.05 was considered statistically significant.Results: The median age of study participants was 57 (25- 96) years. The prevalence of OH was 17.6%. Uncontrolled hypertension (adjusted OR 2.08, 95% CI 1.125- 3.872) and duration of hypertension ≥ 5 years (adjusted OR 2.04, 95% CI 1.069- 3.895) were significantly associated with OH in hypertensive patients.Conclusion: The prevalence of OH among male hypertensive patients was high. Hypertensive patients whose BP was uncontrolled and having had hypertension ≥ 5 years were risk factors of OH.Keywords: orthostatic hypotension, hypertension, prevalence, Ethiopia